2018
DOI: 10.1002/chem.201704752
|View full text |Cite
|
Sign up to set email alerts
|

Epitope‐Targeted Macrocyclic Peptide Ligand with Picomolar Cooperative Binding to Interleukin‐17F

Abstract: The IL-17 cytokine family is associated with multiple immune and autoimmune diseases and comprises important diagnostic and therapeutic targets. This work reports the development of epitope-targeted ligands designed for differential detection of human IL-17F and its closest homologue IL-17A. Non-overlapping and unique epitopes on IL-17F and IL-17A were identified by comparative sequence analysis of the two proteins. Synthetic variants of these epitopes were utilized as targets for in situ click screens against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Two other motifs with high sequence homology (AHHAADAHHA and AHHAHHAAD) were also targeted, yielding consensus PCC sequences of Tyr‐Lys‐Tyr‐Tyr‐Arg (cyYKYYR, L2 ; EC 50 = 218nM) and Tyr‐(4F)Phe‐Tyr‐Arg‐Val (cyY 4F FYRV, L3 ; EC 50 = 540pM) (Figure C). We have previously demonstrated that the qualitative EC 50 values of PCC‐target binding, assayed using methods employed here, approximate (within a factor of 2) the quantitative binding constants (K d ) measured using fluorescence polarization . Thus, we stipulate that these EC 50 values approximate the K d of L1 , L2 , and L3 to HRP2.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Two other motifs with high sequence homology (AHHAADAHHA and AHHAHHAAD) were also targeted, yielding consensus PCC sequences of Tyr‐Lys‐Tyr‐Tyr‐Arg (cyYKYYR, L2 ; EC 50 = 218nM) and Tyr‐(4F)Phe‐Tyr‐Arg‐Val (cyY 4F FYRV, L3 ; EC 50 = 540pM) (Figure C). We have previously demonstrated that the qualitative EC 50 values of PCC‐target binding, assayed using methods employed here, approximate (within a factor of 2) the quantitative binding constants (K d ) measured using fluorescence polarization . Thus, we stipulate that these EC 50 values approximate the K d of L1 , L2 , and L3 to HRP2.…”
Section: Resultssupporting
confidence: 60%
“…We have previously demonstrated that the qualitative EC 50 values of PCC-target binding, assayed using methods employed here, approximate (within a factor of 2) the quantitative binding constants (K d ) measured using fluorescence polarization. 28 Thus, we stipulate that these EC 50 values approximate the K d of L1, L2, and L3 to HRP2.…”
Section: Supporting Information) a Macrocycle Bearing The Sequencementioning
confidence: 99%
“…60,61 Epitope-targeted PCC ligands against the MrkA protein PCC ligands against the four selected epitopes were identied from a combinatorial library of macrocyclic peptides by using the epitope-targeted PCC method. [42][43][44][45] This method exploits non-catalyzed click chemistry via an in situ click screen. For the screen, an alkyne-presenting, one-bead one-compound (OBOC) combinatorial library of approximately 1 M peptide macrocycles with a 5-residue variable region is screened against synthetic variants of the epitopes (SynEps).…”
Section: Resultsmentioning
confidence: 99%
“…Combinatorial in situ click screens were performed as described previously. 44 Briey, 500 mg (representing $1.4 copies of approximately 1 000 000 different compounds) of a combinatorial onebead one-compound libraries was incubated overnight with shaking in TBS buffer (25 mM Tris HCl, 150 mM NaCl, pH 7.6). A preclear to remove beads that bound SAv-AP was performed as follows.…”
Section: Combinatorial Pcc Screeningmentioning
confidence: 99%
See 1 more Smart Citation